Efficacy of robot‐assisted radical cystectomy (RARC) in advanced bladder cancer: results from the International Radical Cystectomy Consortium (IRCC). (22nd May 2014) - Al‐Daghmin, Ali; Kauffman, Eric C.; Shi, Yi; Badani, Ketan; Balbay, M. Derya; Canda, Erdem; Dasgupta, Prokar; Ghavamian, Reza; Grubb, Robert; Hemal, Ashok; Kaouk, Jihad; Kibel, Adam S.; et al.
<x xml:space="preserve">Abstract</x> Objective To characterise the surgical feasibility and outcomes of robot‐assisted radical cystectomy (RARC) for pathological T4 bladder cancer. Patients and Methods Retrospective evaluation of a prospectively maintained International Radical Cystectomy Consortium database was conducted for 1118 patients who underwent RARC between 2003 and 2012. We dichotomised patients based on pathological stage (≤pT3 vs pT4) and evaluated demographic, operative and pathological variables in relation to morbidity and mortality. Results In all, 1000 ≤pT3 and 118 pT4 patients were evaluated. The pT4 patients were older than the ≤pT3 patients (P = 0.001). The median operating time and blood loss were 386 min and 350 mL vs 396 min and 350 mL for p T4 and ≤pT3, respectively. The complication rate was similar (54% vs 58%; P = 0.64) among ≤pT3 and pT4 patients, respectively. The overall 30‐ and 90‐day mortality rate was 0.4% and 1.8% vs 4.2% and 8.5% for ≤pT3 vs pT4 patients (P < 0.001), respectively. The body mass index (BMI), American Society of Anesthesiology score, length of hospital stay (LOS) >10 days, and 90‐day readmission were significantly associated with complications in pT4 patients. Meanwhile, BMI, LOS >10 days, grade 3–5 complications, 90‐day readmission, smoking, previous abdominal surgery and neoadjuvant chemotherapy were significantly associated with mortality in pT4 patients. On multivariate analysis, BMI was an independent predictor of complications in pT4 patients, but not for mortality. Conclusions RARC for pT4 bladder cancer is surgically feasible but entails significant morbidity and mortality. BMI was independent predictor of complications in pT4 patients.